Restorasi Digital Pada Model Kerusakan Citra Aksara Jawa Cetak - Agustinus Rudatyo Himamunanto (AITI, 2016)
Javanese script is an important cultural legacy as it was widely used in a great number of old books. Digital restoration can be used to preserve these books, but the challenge is the script in these old books may be damaged due to age. Digital restoration, which involves such processes as thinning, feature extraction, and pattern matching, can be used to assist in accelerating the manual restoration process. The average success rate of this digital restoration project is only 82,07%, but it is a good start in the digital restoration of damaged print Javanese script.